Analysis of the epidemiological profile and hospitalizations of patients with tuberculosis in the municipality of Pinheiro-Maranhão between 2019-2024 (Research, Society and Development, 2024)
Objective: To analyze the epidemiological profile of patients with tuberculosis, whether they were hospitalized or diagnosed with the disease in the municipality of Pinheiro-Maranhão. Methodology: This is a direct-source documentary study using the Brazilian Unified Health System Information Technology Department (DATASUS) in a cross-sectional epidemiological study of a quantitative nature. Results: 127 confirmed cases and 55,942 hospitalizations for Tuberculosis (TB) were collected during the period 2019 to 2024 in the Municipality of Pinheiro - MA. Divided into topics of hospitalizations and cases by sex, with males having the highest incidence of confirmed cases with 63.78% and females leading the cases of hospitalizations with 57.55%. In addition, cases and hospitalizations by race had the highest incidence of brown people, accounting for 82% and 58% of both variables. The highest incidence of confirmed cases by schooling was between the 1st and 8th grades, with 25.20% of the sample. Hospitalizations and diagnoses by age were more representative of the 20-49 age group. By population vulnerable to the disease, those infected with AIDS were the hardest hit. Hospital costs totaled 49,122,122.17 over six years, while deaths were lower between 2023 and 2024. Final considerations: It can be seen that there is a vast amount of information in the literature about TB. However, the greatest challenge is associated with a health system that can reach, notify and treat TB.